2014
DOI: 10.1016/j.jhydrol.2013.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of different river water level interpolation schemes on modeled groundwater residence times

Abstract: Keywords:River restoration River water level distribution Groundwater residence time Groundwater flow and transport modeling FEFLOW PEST s u m m a r yObtaining a quantitative understanding of river-groundwater interactions is of high practical relevance, for instance within the context of riverbank filtration and river restoration. Modeling interactions between river and groundwater requires knowledge of the river's spatiotemporal water level distribution. The dynamic nature of riverbed morphology in restored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
1
21
0
1
Order By: Relevance
“…Saleh et al (2011) showed that this methodology not only leads to biased assessments of streamaquifer exchanges, but also to biased estimates of the nearriver piezometric head distributions. In addition, Diem et al (2014) recently showed that groundwater residence times are also strongly affected by the estimation of in-stream longitudinal water level distributions. These results are due to the fact that stream-aquifer exchange rates adapt very quickly to changes in surface water levels (Koussis et al, 2007;Maier and Howard, 2011;Rosenberry et al, 2013).…”
Section: The Conductance Model At the Regional Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Saleh et al (2011) showed that this methodology not only leads to biased assessments of streamaquifer exchanges, but also to biased estimates of the nearriver piezometric head distributions. In addition, Diem et al (2014) recently showed that groundwater residence times are also strongly affected by the estimation of in-stream longitudinal water level distributions. These results are due to the fact that stream-aquifer exchange rates adapt very quickly to changes in surface water levels (Koussis et al, 2007;Maier and Howard, 2011;Rosenberry et al, 2013).…”
Section: The Conductance Model At the Regional Scalementioning
confidence: 99%
“…As stream-aquifer exchanges are very responsive to inriver water level fluctuations (Diem et al, 2014;Koussis et al, 2007;Maier and Howard, 2011;Saleh et al, 2011), the assimilation of space borne data and data products in numerical models, like the ones used by Pryet et al (2014), Saleh et al (2011) and (Fig. 5), should enable a better understanding of stream-aquifer interaction at very large scale.…”
Section: Space Borne Approaches: Regional and Continental Scalesmentioning
confidence: 99%
“…The Thur River is the largest river in Switzerland without a retention basin. This leads to a very dynamic discharge regime ranging from 3 to 1100 m 3 s −1 with an average of 47 m 3 s −1 (Diem et al, 2013b(Diem et al, , 2014. The field site (Fig.…”
Section: The Record Project At the Thur River (Switzerland)mentioning
confidence: 99%
“…In addition, more than 80 piezometers (2 inch) were installed during the project (Diem et al, 2013b(Diem et al, , 2014.…”
Section: The Record Project At the Thur River (Switzerland)mentioning
confidence: 99%
See 1 more Smart Citation